al-Usus al-Lughawwiyah Fī Ta`līm al-Lughah al-`Arabiyah Li Ghair an-Nāṭiqīn Bihā Baina an-Naẓariyah Wa at-Taṭbīq: الأسس اللغوية في تعليم اللغة العربية لغير الناطقين بها بين النظرية والتطبيق - Moch. Fajarul Falah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
Teaching Arabic to non-native speakers is one of the scientific matters that hardly anyone leaves in this field. Because Arabic is one of the most used languages in the world after English. Despite the lack of methods for teaching it, the failure of teaching it is due to the way it is taught without taking into account the differences between the language studied and the language of the learners. This is one of the reasons for the difficulty of non-Arabic learners while learning the Arabic language. Arabic language teachers must pay attention to the linguistic foundations and apply a theory related to those foundations, whether it is a constructive theory or an innovative transformational theory. Since the constructivist theory is based on the acquisition of habits, the value of repetition, training, simulation, and memorization must be emphasized in teaching Arabic to foreigners. As for the innovative transformational theory, it holds that the process of understanding and innovation is the rule and not the exception in the use of language, with the exception of some phrases that speakers use without significant change, such as greetings.